The novel CaMKII inhibitor GS-680 reduces diastolic SR Ca leak and prevents CaMKII-dependent pro-arrhythmic activity. (May 2018) - Lebek, S.; Plößl, A.; Baier, M.; Mustroph, J.; Tarnowski, D.; Lücht, C.M.; Schopka, S.; Flörchinger, B.; Schmid, C.; Zausig, Y.; Pagratis, N.; Marchand, B.; et al.
Abstract: Rationale: Ca/calmodulin-dependent protein kinase II (CaMKII) was shown to increase diastolic sarcoplasmic reticulum (SR) Ca leak, which can result in delayed afterdepolarizations and triggered arrhythmias. Since increased CaMKII expression and activity has been mechanistically linked to arrhythmias in human heart failure (HF) and atrial fibrillation (AF), specific strategies aimed at CaMKII inhibition may have therapeutic potential. Objective: We tested the antiarrhythmic and inotropic effects of a novel selective and ATP-competitive CaMKII inhibitor (GS-680). Methods and results: Trabeculae were isolated from right atrial appendage biopsies of patients undergoing cardiac surgery. Premature atrial contractions (PACs) were induced by stimulation with isoproterenol (ISO, 100 nM) at increased [Ca]o (3.5 mM). Interestingly, compared to vehicle, PACs were significantly inhibited by exposure to GS-680 (at 100 and 300 nM). GS-680 also significantly decreased early and delayed afterdepolarizations in isolated human atrial myocytes. Moreover, GS-680 (at 100 or 300 nM) significantly inhibited diastolic SR Ca leak, measured as frequency of spontaneous SR Ca release events (Ca sparks) in isolated human atrial myocytes (Fluo-4 loaded) similar to the well-established peptide CaMKII inhibitor AIP. In accordance, GS-680 significantly reduced CaMKII autophosphorylation (Western blot) but enhanced developed tension after 10 or 30 s pause of electrical stimulation (post-rest behavior). Surprisingly, we found a strong negative inotropic effect of GS-680 in atrial trabeculae at 1 Hz stimulation rate, which was not observed at 4 Hz and abolished by beta-adrenergic stimulation. In contrast, GS-680 did not impair systolic force of isolated ventricular trabeculae from explanted hearts of heart transplant recipients at 1 Hz, blunted the negative force-frequency relationship (1–3 Hz) and significantly increased the Ca transient amplitude. Conclusion: The novel ATP-competitive and selective CaMKII inhibitor GS-680 inhibits pro-arrhythmic activity in human atrium and improves contractility in failing human ventricle, which may have therapeutic implications. Graphical abstract: Highlights: The novel CaMKII inhibitor GS-680 inhibits pro-arrhythmic activity in human atrial trabeculae and myocytes GS-680 potently reduces diastolic SR Ca leak in human cardiomyocytes GS-680 blunts the negative force-frequency relationship of failing human ventricular trabeculae GS-680 increases Ca transient amplitude in failing human ventricular myocytes